PROFIL MANAJEMEN ORGANISASI PERBASI KABUPATEN BLORA - Niko Martin Kartika; Anggit Wicaksono (Unnes Journal of Sport Sciences, 2023)
The success of an organization is marked by the ability of management to see opportunities and opportunities in the future. This study aims to produce: Model of management program implementation in PERBASI (Indonesian Basketball Association) Blora Regency; Model of management system and basketball coaching in PERBASI Blora Regency. This is a qualitative research study looking at different aspects of sport organization in this region. The research subjects are: 9 members of PERBASI Blora, 5 basketball coaches, 10 Blora District basketball athletes (16-21 years old). The results showed that: Branch manager of PERBASI in carrying out organizational management does not have a system of implementing the program, The basketball coaching system at Blora has not been designed to be sustainable, basketball competition in Blora Regency has not yet been held. The management system of the organization, basketball and sports in Blora Regency is not yet running well. The conclusion of the research states that the implementation of basketball management and coaching in Blora Regency has not been programmed efficiently. Results of this research suggest that all parties involved in a basketball sports coaching system in Blora Regency should cooperate in implementing management programs.